2013
DOI: 10.5194/bg-10-6199-2013
|View full text |Cite
|
Sign up to set email alerts
|

Estimating carbonate parameters from hydrographic data for the intermediate and deep waters of the Southern Hemisphere oceans

Abstract: Abstract. Using ocean carbon data from global datasets, we have developed several multiple linear regression (MLR) algorithms to estimate alkalinity and dissolved inorganic carbon (DIC) in the intermediate and deep waters of the Southern Hemisphere (south of 25 • S) from only hydrographic data (temperature, salinity and dissolved oxygen). A Monte Carlo experiment was used to identify a potential density (σ θ ) of 27.5 as an optimal break point between the two regimes with different MLR algorithms. The algorith… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
34
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 59 publications
6
34
0
Order By: Relevance
“…Another feature that agrees with the hypothesis of upwelling intensification is the shoaling of the ASD following the path of upwelling of the UCDW layer. This feature was also described by Bostock et al (2013) in an oceanic climatology of Ar and could be due to the naturally lower buffer capacity of the UCDW layer (low value of TA / DIC ≈ 1.043) with respect to upper layers (TA / DIC ≈ 1.06 in the AASW layer). However, the greatest shoaling of the ASD in the UCDW layers compared to the AAIW layer (Table 6) is consistent with the upwelling of UCDW, as both water masses have similar TA / DIC ratios (TA / DIC ≈ 1.043 for the UCDW layer and TA / DIC ≈ 1.042 for the AAIW layer).…”
Section: Discussionsupporting
confidence: 56%
“…Another feature that agrees with the hypothesis of upwelling intensification is the shoaling of the ASD following the path of upwelling of the UCDW layer. This feature was also described by Bostock et al (2013) in an oceanic climatology of Ar and could be due to the naturally lower buffer capacity of the UCDW layer (low value of TA / DIC ≈ 1.043) with respect to upper layers (TA / DIC ≈ 1.06 in the AASW layer). However, the greatest shoaling of the ASD in the UCDW layers compared to the AAIW layer (Table 6) is consistent with the upwelling of UCDW, as both water masses have similar TA / DIC ratios (TA / DIC ≈ 1.043 for the UCDW layer and TA / DIC ≈ 1.042 for the AAIW layer).…”
Section: Discussionsupporting
confidence: 56%
“…It has been shown that such algorithms often fail in coastal waters due to the strong influence that coastal processes 15 have on the distribution of TA (Bostock et al, 2013;Cai et al, 2010). Our results confirmed that such open ocean models are not necessarily optimal for predicting TA in coastal waters and their use can result in large systematic errors in some regions (Fig.…”
supporting
confidence: 81%
“…dissolved organic inputs and 35 biological processes such as calcification and organic matter production). Thus, these relationships may not be robust in coastal regions (Bostock et al, 2013;Cai et al, 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used multiple linear regression models (MLR) to estimate inorganic carbon variables from hydrographic measurements (Juranek et al, 2009(Juranek et al, , 2011Kim et al, 2010;Alin et al, 2012;Bostock et al, 2013;Williams et al, 2016;Carter et al, 2017). These were applied to different data sets (hydrographic surveys, time-series, profiling floats, climatology) in order to reconstruct estimates of the natural variability of carbon variables.…”
Section: Introductionmentioning
confidence: 99%